Research and Design of a New Horizontal Lower Limb Rehabilitation Training Robot. (27th January 2016) - Guo, Bingjing; Han, Jianhai; Li, Xiangpan; Fang, Taotao; You, Aimin
This project focuses on the design of one robot to help long-time bedridden patients complete their daily leg rehabilitation training while lying in bed. Based on an analysis of many rehabilitation training modes and integrated with a traditional Chinese medicine (TCM) massage technique, a new horizontal lower limb rehabilitation training robot with four degrees of freedom is presented in this paper. The mechanical structural design, kinematic calculation and control system are introduced in detail. A robot prototype is fabricated and rehabilitation training experiments are carried out. The experimental results show that the robot can satisfy the requirements of a variety of rehabilitation training modes and has a certain degree of rehabilitation effectiveness.